An Experimental Investigation of the Travel and Tourism Sector in Nepal: The Effects of Social Networking Management on Hospitality Industries - Karna, Santosh Kumar; Singh, Kabindra Raj (Darul Yasin Al Sys, 2025)
The purpose of this study is to look into, analyze, and evaluate the social media marketing strategies employed by the travel and tourism sector in Nepal. The study looks at the current state of social media advertisement in Nepal in relation to travel middlemen and focuses on the main areas: (a) social media use in travel middleman business; (b) social media's impact on prospects and how they respond to social media sites (SMSs). Using a mixed study strategy, the paper combined the initial inquiries with additional information from searches from the former's SMSs. The intermediates, or principal travel-tourism industry hub of Nepal, were selected through an easy sampling method. According to the report, travel professionals are using social media more frequently to communicate with clients about prices and products—information that consumers are particularly interested in and responsive to. The most popular social media platforms among middlemen and consumers were Facebook by itself and Facebook in conjunction with other platforms, and SMSs had a significant impact on the majority of customers' purchases of mixed-category travel products. The most important thing that SMSs give consumers is helping them remember the product details, reviews, and recommendations they were looking for. Travel managers may find the insights helpful in bolstering their social media advertisements.